A Multilevel Examination of Pro-Environmental Behavior and Its Impact on Hotel Performance: Evidence from Green Ho-tels in Indonesia (Pusat Riset dan Inovasi Nasional, 2026)
This study adopts a multilevel analytical framework to investigate the implementation of pro-environmental behavior (PEB) and its implications for organizational performance in the context of Green Hotels in Semarang, Indonesia. Grounded in Social Exchange Theory, the Ability-Motivation-Opportunity (AMO) framework, and Social Identity Theory, the research explores how PEB at both individual and departmental levels contributes to environmental, financial, and operational performance metrics. Special attention is directed toward the role of young talent employees (<35 years) as strategic change agents in sustainability transitions.A qualitative case study methodology was employed, involving 35 informants across five certified Green Hotels. Data were collected through semi-structured interviews, direct observations, focus group discussions, and documentary analysis. Thematic coding and cross-level analysis were conducted using NVivo software to ensure methodological rigor and analytical depth. Findings reveal that departmental-level PEB exhibits a more structured and consistent implementation pattern, exerting a stronger impact on environmental and financial outcomes. In contrast, individual-level PEB predominantly influences operational efficiency. Importantly, the cross-level interaction between individual and departmental PEB generates multiplicative effects on guest satisfaction and synergistic effects on environmental performance. Five organizational enablers—executive support, pro-environmental culture, performance-based rewards, sustained training, and participatory decision-making—emerge as critical in optimizing young talent engagement in green practices. This study advances multilevel theorizing in green human resource management (GHRM) and provides actionable insights for practitioners seeking to institutionalize sustainability within hospitality operations in emerging markets.